2019
DOI: 10.3390/mi11010031
|View full text |Cite
|
Sign up to set email alerts
|

3D Printed Wavy Scaffolds Enhance Mesenchymal Stem Cell Osteogenesis

Abstract: There is a growing interest in developing 3D porous scaffolds with tunable architectures for bone tissue engineering. Surface topography has been shown to control stem cell behavior including differentiation. In this study, we printed 3D porous scaffolds with wavy or linear patterns to investigate the effect of wavy scaffold architecture on human mesenchymal stem cell (hMSC) osteogenesis. Five distinct wavy scaffolds were designed using sinusoidal waveforms with varying wavelengths and amplitudes, and orthogon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 90 publications
1
23
0
Order By: Relevance
“…Morphological structure, gene expression, and cell function, proliferation, and differentiation of cells in 3D are different than the cells in 2D [115]. Furthermore, the 3D scaffold can be able to augment the production of osteogenesis [116] and chondrogenesis as compared to 2D scaffold and thus is being used more frequently in osteochondral tissue engineering [117,118].…”
Section: Interventions In Actin Remodeling and Their Effect On Msc DImentioning
confidence: 99%
“…Morphological structure, gene expression, and cell function, proliferation, and differentiation of cells in 3D are different than the cells in 2D [115]. Furthermore, the 3D scaffold can be able to augment the production of osteogenesis [116] and chondrogenesis as compared to 2D scaffold and thus is being used more frequently in osteochondral tissue engineering [117,118].…”
Section: Interventions In Actin Remodeling and Their Effect On Msc DImentioning
confidence: 99%
“…However, most studies in tissue engineering had focused on attachment, growth, and proliferation of the constituent cells, neglecting the collective migratory behavior in response to the different cues from the microenvironments of the engineered tissue. Shen Ji et al [ 13 ] investigated the effect of wavy scaffold architecture on the osteogenesis of human mesenchymal stem cell (hMSC) by ultilizing 3D porous scaffolds that featured curved or linear patterns. They found that hMSCs on wavy patterns spreaded by following the curvature form provided by the wavy patterns, exhibiting elongated morphology and mature focal adhesion points.…”
Section: Introductionmentioning
confidence: 99%
“…These constraints include: 1) limited number of available bioink solutions and lack of thorough characterization of their biological and physiomechanical properties [10,17]; 2) poor understanding of the correlation between printed architecture and the ultimate tissue function [18,19]; 3) limitations on the quality of imaging techniques [20,21] and available bioprinters [22]; 4) complex and rather expensive processes involved pre, during, and post-bioprinting [22]; 5) suboptimal, non-specialized printing software and their often incompatibilities [23].There are eight articles published in this Special Issue composed of four research papers and four review papers. The research articles focus on the influence of electron beam (E-beam) sterilization on in vivo degradation of composite filaments [24], enhancing osteogenic differentiation of stem cells using 3D printed wavy scaffolds [25], the development of a scaffold-free bioprinter [26], and the fabrication of multilayered vascular constructs with a curved structure and multi-branches [27]. Kang et al investigated the effect of E-beam sterilization on the degradation of β-tricalcium phosphate/polycaprolactone (β-TCP/PCL) composite filaments in a rat subcutaneous model for 24 weeks [24].…”
mentioning
confidence: 99%
“…There are eight articles published in this Special Issue composed of four research papers and four review papers. The research articles focus on the influence of electron beam (E-beam) sterilization on in vivo degradation of composite filaments [24], enhancing osteogenic differentiation of stem cells using 3D printed wavy scaffolds [25], the development of a scaffold-free bioprinter [26], and the fabrication of multilayered vascular constructs with a curved structure and multi-branches [27]. Kang et al investigated the effect of E-beam sterilization on the degradation of β-tricalcium phosphate/polycaprolactone (β-TCP/PCL) composite filaments in a rat subcutaneous model for 24 weeks [24].…”
mentioning
confidence: 99%
See 1 more Smart Citation